2021
DOI: 10.3389/fmicb.2021.785351
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis natto Derivatives Inhibit Enterococcal Biofilm Formation via Restructuring of the Cell Envelope

Abstract: Enterococcus faecalis is considered a leading cause of hospital-acquired infections. Treatment of these infections has become a major challenge for clinicians because some E. faecalis strains are resistant to multiple clinically used antibiotics. Moreover, the presence of E. faecalis biofilms can make infections with E. faecalis more difficult to eradicate with current antibiotic therapies. Thus, our aim in this study was to investigate the effects of probiotic derivatives against E. faecalis biofilm formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 66 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Among them, Bacillus subtilis natto, as a sort of the most important probiotics, have shown obvious antibacterial activity. Researches have shown the inhibitory effect of B. subtilis natto derivatives on Enterococcus faecalis that is considered to be the leading cause of hospital-acquired infections ( Lin et al, 2021 ). Some derivatives from the culture fluid of B. subtilis natto may be useful for controlling E. faecalis biofilms.…”
Section: Pharmacological Actions Of Nattomentioning
confidence: 99%
“…Among them, Bacillus subtilis natto, as a sort of the most important probiotics, have shown obvious antibacterial activity. Researches have shown the inhibitory effect of B. subtilis natto derivatives on Enterococcus faecalis that is considered to be the leading cause of hospital-acquired infections ( Lin et al, 2021 ). Some derivatives from the culture fluid of B. subtilis natto may be useful for controlling E. faecalis biofilms.…”
Section: Pharmacological Actions Of Nattomentioning
confidence: 99%
“…Bacillus spp. are Gram-positive and spore-forming bacteria commonly found in soil and plants, have the advantage of being highly stable in acidic environments, and can thrive in various food matrices [ 40 , 41 , 42 , 43 , 44 ]. In our earlier study, we assessed ten bacterial isolates obtained from bee bread (BB) and bee pollen (BP) to determine their potential as probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that FSFs can significantly alleviate hyperlipidemia and lower the likelihood of developing atherosclerosis and cardiovascular pathologies [14]. The Bacillus subtilis natto derivatives exhibit a significant inhibitory effect towards Enterococcus faecalis, which is recognized as a major etiology of nosocomial infections [15]. Yang et al examined Lactococcus acidophilus fermented soymilk and found that the FSFs showed significantly higher antioxidant activity than non-fermented products [16].…”
Section: Introductionmentioning
confidence: 99%